2023
DOI: 10.1002/tpg2.20363
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in a tepary bean (Phaseolus acutifolius A. Gray) diversity panel reveals loci associated with biotic stress resistance

Abstract: Tepary bean (Phaseolus acutifolius A. Gray), indigenous to the arid climates of northern Mexico and the Southwest United States, diverged from common bean (Phaseolus vulgaris L.), approximately 2 million years ago and exhibits a wide range of resistance to biotic stressors. The tepary genome is highly syntenic to the common bean genome providing a foundation for discovery and breeding of agronomic traits between these two crop species. Although a limited number of adaptive traits from tepary bean have been int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 132 publications
0
2
2
Order By: Relevance
“…The grouping of landraces like Uchokwane (G50) and Zimbabwe landrace (G45) with released and breeding varieties in Clusters 1 and 2 signifies the presence of admixtures that could have arisen due to historical exchanges of seeds through the informal seed system or the exchange of germplasm between breeding programs. The number of subpopulations in our study was slightly lower than the six subpopulations reported by Bornowski et al [ 35 ]. This could be attributed to differences in the diversity panels and genotyping platform used.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The grouping of landraces like Uchokwane (G50) and Zimbabwe landrace (G45) with released and breeding varieties in Clusters 1 and 2 signifies the presence of admixtures that could have arisen due to historical exchanges of seeds through the informal seed system or the exchange of germplasm between breeding programs. The number of subpopulations in our study was slightly lower than the six subpopulations reported by Bornowski et al [ 35 ]. This could be attributed to differences in the diversity panels and genotyping platform used.…”
Section: Discussioncontrasting
confidence: 90%
“…arisen due to historical exchanges of seeds through the informal seed system or the exchange of germplasm between breeding programs. The number of subpopulations in our study was slightly lower than the six subpopulations reported by Bornowski et al [35]. This could be attributed to differences in the diversity panels and genotyping platform used.…”
Section: Plos Onecontrasting
confidence: 86%
See 1 more Smart Citation
“…The original cross in the development of USDA Fortuna (tested as TARS-Tep 93), G40022 (TDP-13)/G40029 (TDP-18), was completed in a screenhouse at the Tropical Agriculture Research Station (TARS) in Mayaguez, Puerto Rico (PR), in 2014, and parents were selected out of the Tepary Diversity Panel (TDP) (Bornowski et al, 2023) (Miklas et al, 1994), common bacterial blight resistance (Urrea et al, 1999), heat tolerance (Rainey & Griffiths, 2005), and a small yellow round seed type. G40022 was collected by Howard Scott Gentry in 1966 in Newfields, AZ, along the U.S.-Mexico border, at approximately 816 m asl.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, little is known about the inheritance and mechanisms responsible for resistance or tolerance to A. obtectus in common beans. Only three QTL mapping reports [5,12,13], and two inheritance studies have been reported in biparental crosses, comprising a segregation 15S: 1R by Kornegay and Cardona [8] and 3R: 1S by Jiménez-Galindo et al [14]. In the first study of QTLs, the authors found three QTLs to have resistance against A. obtectus on chromosomes Pv04 and Pv06.…”
Section: Introductionmentioning
confidence: 99%